Aircraft Interior Comfort and Design - Vink, P. (Peter); Brauer, Klaus (Boca Raton, Fl. : CRC Press, 2011)
'Containing the latest knowledge regarding aircraft interior comfort, this book reviews research based on a unique study among 10,000 passengers. It includes tips on passenger likes and dislikes as well as an overview of the current scientific demands for passenger seats and comfort. Although recognized as an area in need of improvement, currently no resource pulls recent research together and presents in a convenient format. Until now. This book provides what every scientist, designer, and manufacturer working in the field of aircrafts or airliners should know about comfort'--
'This book is important for those working in the aircraft interior industry as it contains all the information about theories on comfort, the voice of the passenger based on a research among 10,000 passengers in 2009 and specific tips on what the passenger likes and dislikes and it gives an overview on the latest scientific demands for passenger seats'--
Includes bibliographical references and index.
Keywords: Aircraft cabins -- Human factors; Interior decoration -- Human factors; Air travel -- Public opinion